Evaluating the combined effects of mobile computerized CBT and post-learning oscillatory modulation on self-esteem: a randomized controlled trial - Limor Shtoots; Asher Nadler; Avi Gamoran; Daniel A. Levy; Guy Doron (Scientific Reports)
Abstract Self-esteem, crucial for psychological well-being, can be enhanced through targeted interventions like cognitive behavioral therapy (CBT). However, traditional CBT faces various accessibility barriers. Digital health interventions such as computerized CBT and mobile health (mHealth) applications offer potential solutions. Recent research suggests that brain oscillations, particularly theta rhythms, play a key role in memory consolidation. Combining computerized CBT with post-learning theta rhythm modulation may optimize and stabilize improvements in self-esteem and promote neuro-wellbeing. This six-month longitudinal study aimed to evaluate the synergistic effects of a computerized CBT intervention (GGSE) combined with post-training theta rhythm brain modulation on improving self-esteem in young adults with low self-esteem. Participants were randomly allocated to three groups: GGSE + theta audio–visual entrainment (AVE) with Cranio-Electro Stimulation (CES), GGSE + beta AVE + CES (active control), and GGSE only (control). The intervention lasted three weeks. Assessments of self-esteem, maladaptive beliefs, and mood were conducted at baseline, 21 days, 42 days, and six months post-baseline. Although post-treatment oscillatory entrainment did not enhance the long-term efficacy of the intervention, significant treatment effects persisted for six months across all groups. These results support the potential long-term efficacy of brief, game-like, digital CBT approaches for improving self-esteem.